PRODUCT DATA MANAGEMENT DALAM KAITAN DENGAN CAD/CAM - Bernardo Nugroho Yahya (Institute of Research and Community Outreach - Petra Christian University, 2004)
The future industry is the one who can manage the information system. Today, communication technology and distributed system computerization already have the ability to implement system that able to exchange and share information between different users. Product Data Management (PDM) is an up-to-date and excellent method on managing the exchange and share of information. PDM is able to integrate and manage data analyzing process and documentation of the related product component physically. By adjusting the CAD/CAM on certain condition, the PDM will function maximally by using the information based on STEP (Standard for the Exchange of Product Data model). This article will explain the relationship between PDM system and CAD/CAM on industry. Abstract in Bahasa Indonesia : Sistem informasi merupakan ujung tombak sebuah perusahaan yang unggul di masa depan. Komputerisasi dengan sistem yang terdistribusi dan teknologi komunikasi saat ini memiliki kemampuan untuk mengimplementasikan sistem yang dapat menukar dan men-share informasi antar user yang berbeda. Teknologi yang mendapat cukup perhatian luas dalam hal pertukaran dan sharing informasi ini adalah Product Data Management (PDM). PDM dapat mengintegrasikan dan mengatur proses pengolahan data dan dokumen teknik yang berhubungan dengan komponen fisik produk yang bersangkutan. PDM akan berfungsi maksimal apabila kesesuaian dengan CAD/CAM diatur sedemikian rupa, dihubungkan dengan informasi berbasiskan STEP (Standard for the Exchange of Product Data model). Artikel ini akan menjelaskan hubungan antara sistem PDM dengan CAD/CAM dalam industri. Kata kunci: PDM, Manajemen Data, CAD/CAM, STEP.